2016
DOI: 10.1002/biot.201600365
|View full text |Cite
|
Sign up to set email alerts
|

Protease substrate profiling using bacterial display of self‐blocking affinity proteins and flow‐cytometric sorting

Abstract: Proteases are involved in fundamental biological processes and are important tools in both biotechnological and biomedical research. An important property of proteases is to discriminate among potential substrates. Here, a new method for substrate profiling of proteases is presented. The substrates are displayed between two anti-idiotypic affinity domains on the Gram-positive bacterium Staphylococcus carnosus. The first domain functions as a reporter tag and has affinity for a labeled reporter protein, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Upon addition of protease, variants with a functional substrate will be cleaved within the linker, resulting in release of the blocking domain and binding of the fluorescent reporter molecule. Using substrate libraries for tobacco etch virus (TEV) protease and matrix metalloprotease (MMP)-1, the substrate profiles for the respective protease were identified and several new peptides were isolated for MMP-1 that were processed with up to eightfold higher catalytic activity compared with previously reported substrates (Sandersjoo et al 2017 ).…”
Section: Peptide and Protein Libraries Displayed On S Carnmentioning
confidence: 99%
“…Upon addition of protease, variants with a functional substrate will be cleaved within the linker, resulting in release of the blocking domain and binding of the fluorescent reporter molecule. Using substrate libraries for tobacco etch virus (TEV) protease and matrix metalloprotease (MMP)-1, the substrate profiles for the respective protease were identified and several new peptides were isolated for MMP-1 that were processed with up to eightfold higher catalytic activity compared with previously reported substrates (Sandersjoo et al 2017 ).…”
Section: Peptide and Protein Libraries Displayed On S Carnmentioning
confidence: 99%
“…Proteases play important roles in fundamental biological processes and are critical important in biotechnological and biomedical research. Dr. John Löfblom and colleagues [5] introduce a novel method for protease substrate profiling using bacterial display of self-blocking affinity proteins and flow-cytometric sorting, and they have successfully demonstrated that this method has potential as an efficient tool for substrate profiling.…”
Section: Jing Zhu and Uta Goebelmentioning
confidence: 99%
“…Obviously, the diversity of substrates makes the mapping of one or more sites technically difficult and time-consuming. Several in vivo methods have been exploited to investigate the substrate specificity of peptide–substrate proteases in a high-throughput manner, such as the phage display system [ 21 ], the bacterial display system [ 22 ] and the yeast display system based analysis methods [ 18 , 23 ], whereas protein–substrate proteases, like the SUMO protease, have never been reported in these systems.…”
Section: Introductionmentioning
confidence: 99%